Response of Soil Enzyme and Root Activities of Tea Cultivars Under Elevated Temperature and Carbon Dioxide - Rahman, Ajmeri Sultana; Barukial, Jayanta; Sarmah, Satya Ranjan; Baruah, Rupanjali Deb; Bhattacharjee, Abhilash (Asian Journal of Biological and Life Sciences, 2025)
Aim: The experiment aimed to investigate the root activity of the tea plant as well as the Nitrate Reductase (NR) and Dehydrogenase Activity (DHA) of the tea rhizosphere soil. Materials and Methods: Two Open Top Chamber (OTC) facilities of diameter eight meter each were used in the experimental setup to elevate the CO2 and temperature. With a CO2 concentration of 550 ppm, OTC-1 (eTemp+eCO2) had both a higher temperature and CO2 than OTC-2 (eTemp), which just had a higher temperature. The temperature was 1.5-2°C warmer than the surrounding air. Inside the OTCs, four tea cultivars (TV1, TV20, TV22, and TV23) were planted, and soil samples from the rhizosphere were taken regularly. Results: The findings showed that the overall soil nitrate reductase activity after 300 hr of enrichment, showed no significant difference (p>0.05) in both treatments. In contrast, soil DHA showed a substantial increase (p<0.001) in eTemp+eCO2 treatment after 300 hr of enrichment. Similarly, after 300 hr of enrichment, the overall root activity showed significant increase (p<0.001) in eTemp+eCO2 treatment. Similarly, when the data were analysed cultivar-wise, after 300 hr of treatment, each of the cultivars TV1, TV20, TV22, and TV23 showed a significant variation in root activity under eTemp+eCO2 treatment. Conclusion: The experimental investigation indicates that while soil nitrate reductase activity did not change, higher temperature and CO2 did change the overall soil dehydrogenase activity as well as the root activity of the tea plant.
Keywords: Climate change; Dehydrogenase activity; Enzyme; Nitrate reductase; Rhizosphere; Tea